Weaning from tracheostomy in subjects undergoing pulmonary rehabilitation - Pasqua, Franco; Nardi, Ilaria; Provenzano, Alessia; Mari, Alessia (Multidisciplinary respiratory medicine, 2019)
Background: Weaning from tracheostomy has implications in management, quality of life, and costs of ventilated patients. Furthermore, endotracheal cannula removing needs further studies. Aim of this study was the validation of a protocol for weaning from tracheostomy and evaluation of predictor factors of decannulation. Methods: Medical records of 48 patients were retrospectively evaluated. Patients were decannulated in agreement with a decannulation protocol based on the evaluation of clinical stability, expiratory muscle strength, presence of tracheal stenosis/granulomas, deglutition function, partial pressure of CO2, and PaO2/FiO2 ratio. These variables, together with underlying disease, blood gas analysis parameters, time elapsed with cannula, comordibity, Barthel index, and the condition of ventilation, were evaluated in a logistic model as predictors of decannulation. Results: 63 % of patients were successfully decannulated in agreement with our protocol and no one needed to be re-cannulated. Three variables were significantly associated with the decannulation: no pulmonary underlying diseases (OR = 7.12; 95 % CI 1.2–42.2), no mechanical ventilation (OR = 9.55; 95 % CI 2.1–44.2) and period of tracheostomy ≤10 weeks (OR = 6.5; 95 % CI 1.6–27.5). Conclusions: The positive course of decannulated patients supports the suitability of the weaning protocol we propose here. The strong predictive role of three clinical variables gives premise for new studies testing simpler decannulation protocols.